Cobalt Doping on Zirconium Titanate as a Potential Photocatalyst with Visible-Light-Response - Emilya Faridatul Sulaikhah; Rian Kurniawan; Mokhammad Fajar Pradipta; Wega Trisunaryanti; Akhmad Syoufian (Universitas Gadjah Mada, 2020)
Synthesis of cobalt-doped zirconium titanate (Co-doped ZrTiO4) as a potential photocatalyst with visible-light-response had been conducted. Materials used in this research were titanium tetraisopropoxide (TTIP) as a precursor of TiO2, ZrO2 as another semiconductor for coupling, and CoSO4·7H2O as the source of cobalt dopant. The composite was prepared by the sol-gel method with various cobalt contents and calcination temperatures. Composites with various Co dopant contents (0, 1, 3, 5, 7, and 9% (Co wt./Ti wt.)) were calcined at 500 °C for 4 h. In addition, the composite with 5% of dopant content was calcined at 700 and 900 °C to observe the influence of calcination temperature. All samples were characterized by using X-ray powder diffraction method (XRD), Fourier-transform infrared spectroscopy (FTIR), specular reflectance UV-Vis spectroscopy (SRUV), and scanning electron microscopy equipped with X-ray energy dispersive spectroscopy (SEM-EDS). Co-doped ZrTiO4 with the lowest bandgap (2.94 eV) was achieved in a sample containing 3% of cobalt content calcined at 500 °C.